Clinical characteristics of a KIF21A mutation in a Chinese family with congenital fibrosis of the extraocular muscles type 1. Issue 38 (September 2017) - Chen, Huiqiong; Liu, Tangbing; Zeng, Zhenhai; Wang, Yufei; Lin, Yuanyuan; Cheng, Lulu; Pan, Qintuo; Gu, Feng; Song, Zongming; Zhang, Zongduan
Abstract : Abstract: The aim of the study is to characterize the clinical ocular phenotype with congenital fibrosis of the extraocular muscles type 1 (CFEOM1) and to confirm whether the kinesin family member 21A ( KIF21A ) mutation was the pathogenic gene in this Chinese family. Three affected individuals and 2 asymptomatic kinsfolk from a Chinese family underwent comprehensive ophthalmic examinations, orbital computerized tomography (CT), and postoperative histological examinations were performed in the proband. All the recruited members were screened for 3 exons (8, 20, and 21) of KIF21A mutations using the polymerase chain reaction (PCR) amplification and direct sequencing of corresponding PCR products. All patients shared the clinical characteristics including bilateral ophthalmoplegia, blepharoptosis, hypertropic, and exotropic position with inability to raise either eye above the midline and a chin-up head position. Direct DNA sequence analysis from the affected members revealed a missense mutation in KIF21A (c.2860C>T, p.R954W). The unaffected members did not harbor the p.R954W mutation. The candidate mutation was not present in multiple web-accessible and in-house exome databases. The p.Arg954Trp mutation of KIF21A was the causative mutation in this Chinese pedigree with CFEOM1.